Anti-Inflammatory Activity Test of Combination Ethanol Extract of Papaya Leaves (Carica papaya L.) and Celery Leaves (Apium Graveolens L.) in Male White Rats - Muhammad Athfal Nuransyah; Neli Syahida Ni’ma (Journal of Science and Technology Research for Pharmacy, 2024)
Background: Papaya leaves (Carica papaya L.) and celery leaves (Apium graveolens L.) are suspected to have anti-inflammatory activity due to their secondary metabolites such as flavonoids, tannins, saponins, alkaloids, steroids, and terpenoids. Aim: This study aims to determine the anti-inflammatory activity of a combination of ethanol extracts of papaya leaves and celery leaves compared to the use of single extracts and standard anti-inflammatory drugs. Material and Methods: The method used is the Rat Hit Paw Edema, which induces inflammation in the rat paw using carrageenan. Twenty-five rats were divided into 5 treatment groups: negative control (CMC-Na 1%), positive control (Na Diclofenac 4.5 mg/kgBW), papaya leaf ethanol extract 50 mg/kgBW, celery leaf ethanol extract 200 mg/kgBW, and a combination of papaya leaf ethanol extract 25 mg/kgBW and celery leaf ethanol extract 100 mg/kgBW. Data collection was done by measuring the paw thickness using calipers at 30, 60, 120, 180, 240, 360, and 480 minutes after carrageenan injection. Data were analyzed by calculating the percentage of inflammation, percentage inhibition, anti-inflammatory percentage, and statistical tests to determine the effectiveness of the extract combination. Results: Phytochemical screening results showed that the ethanol extract of papaya leaves contains flavonoids, tannins, saponins, alkaloids, and steroids, while the ethanol extract of celery leaves contains flavonoids, tannins, saponins, and steroids. The combination of ethanol extracts of papaya and celery leaves showed the highest anti-inflammatory effect at 20.80%, compared to papaya leaf extract at 16.40%, celery leaf extract at 16.93%, and the positive control at 18.75%. Conclusion: Statistical analysis showed that the combination of extracts had a synergistic effect, with One Way Anova and LSD results being significantly different compared to the use of single extracts.